A mixed neoplasm of intraosseous hemangioma with an ameloblastoma: a case of collision tumor or a rare variant? - Harshvardhan Shridhar Jois; Mohan Kumar K.P; Mandali Satish Kumar; Shefali Waghrey (Clinics and Practice, 2011)
Hemangiomas of the head and neck are considered to be benign tumors of infancy that are characterized by a rapid growth phase with endothelial cell proliferation, followed by gradual involution. Central hemangiomas are a rare occurrence and even rarer are the hybrid tumors of central hemangiomas with odontogenic tumors such as ameloblastomas. This paper reports a case of one such hybrid tumor in a middle aged adult clinical presenting as a mandibular swelling with indistinct mixed radiographic presentation and histopathologically comprising of intimately associated hemangiomatous vascular channels and typical ameloblastic areas. To the authors’ knowledge this is the sixth case of such a hemangiomatous ameloblastoma which has been reported till date.